Short-term changes in soil pore size distribution: Impact of land use - Jensen, Johannes L.; Schjønning, Per; Watts, Christopher W.; Christensen, Bent T.; Munkholm, Lars J. (Soil & tillage research, 2020)
•The rate of change in pore size distribution was quantified.•It was faster to degrade than to restore a complex soil structure.•Introducing grassland in degraded soil may induce densification in the short-term. Changes in land use affect the pore size distribution (PSD) of the soil, and hence important soil functions such as gas exchange, water availability and plant growth. The objective of this study was to investigate potentially damaging and restorative soil management practices on soil pore structure. We quantified the rate of change in PSD six years after changes in land use taking advantage of the Highfield land-use change experiment at Rothamsted Research. This experiment includes short-term soil degradation and restoration scenarios established simultaneously within long-term contrasting treatments that had reached steady-state equilibrium. The land-use change scenarios comprised conversion to grassland of previously arable or bare fallow soil, and conversion of grassland to arable and bare fallow soils. In the laboratory, we exposed intact soil cores (100 cm3) to matric potentials ranging from −10 hPa to -1.5 MPa. Based on equivalent soil mass, the plant available water capacity decreased after conversion from grassland, whereas no change was observed after conversion to grassland. Structural void ratio decreased after termination of grassland and introduction of grassland in bare fallow soil, while no change was seen when changing arable to grassland. Consequently, it was faster to degrade than to restore a complex soil structure. The study illustrates that introducing grassland in degraded soil may result in short-term increase in soil density.